2017
DOI: 10.14218/erhm.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Bitter Melon (Momordica charantia L.) Ethanol Extract and Its Fractions on Pancreatic Cancer Cells in vitro

Abstract: IntroductionPancreatic cancer (PC) is the fourth most lethal form of cancer in Western society, with mortality closely mirroring incidence and an overall 5-year survival of less than 7%. 1,2 Upon diagnosis, only 20% of patients are eligible for surgery, the only potential cure to date, with the remainder in advanced stages of the disease.Surgery is invasive due to the physical location of the pancreas and is often used as a treatment option in combination with chemotherapy. Despite this, a majority of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…The results of this study have demonstrated that the active anticancer ingredient(s) from the green succulent fruit in M. charantia is ethanol soluble and several studies have employed the same procedure in preparing the extracts which are highly e cacious in treating other diseases successfully including diabetes and cancer [15,19,35]. In the present study, both low and high doses of the MC ethanol extract and K-J had no effect on the viability of healthy MCF-10A breast cell lines compared to cisplatin which killed over 60% of the cells after 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The results of this study have demonstrated that the active anticancer ingredient(s) from the green succulent fruit in M. charantia is ethanol soluble and several studies have employed the same procedure in preparing the extracts which are highly e cacious in treating other diseases successfully including diabetes and cancer [15,19,35]. In the present study, both low and high doses of the MC ethanol extract and K-J had no effect on the viability of healthy MCF-10A breast cell lines compared to cisplatin which killed over 60% of the cells after 24 hours of treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Asam 3,24,25,26,26,7,23trione yang diperoleh dari ekstrak metanol buah pare memiliki aktivitas sitotoksik terhadap sel kanker hati HepG2 dengan IC50 >100 µM (Hen et al, 2010). Cucurbitacin B diperoleh dari ekstrak etanol buah pare dan memiliki aktivitas sitotoksik terhadap sel kanker pankreas HPDE dan MiaPaCa2 dengan GI50 masing-masing 939,1 μg/mL dan 516,5 μg/mL (Richmond et al, 2017).…”
Section: Pendahuluanunclassified